How different are the wage curves for formal and informal workers? Evidence from Turkey - Badi H. Baltagi; Yusuf Soner Baskaya; Timur Hulagu (Institute for the Study of Labor (IZA), 2012)
This paper presents wage curves for formal and informal workers using a rich individual level data for Turkey over the period 2005-2009. The wage curve is an empirical regularity describing a negative relationship between regional unemployment rates and individuals' real wages. While this relationship has been well documented for a number of countries including Turkey, less attention has focused on how this relationship differs for informal versus formal employment. This is of utmost importance for less developed countries where informal employment plays a significant role in the economy. Using the Turkish Household Labor Force Survey observed over 26 NUTS-2 regions, we find that real hourly wages of informal workers in Turkey are more sensitive to variations in regional unemployment rates than wages of formal workers. This is true for all workers as well as for different gender and age groups.
Keywords: C26; J30; J60; O17; 330; formal/informal employment; wage curve; regional labor markets; Lohnkurve; Informeller Sektor; Regionaler Arbeitsmarkt; Türkei